2022
DOI: 10.5811/westjem.2022.3.54680
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Novel Statewide Network to Support Emergency Department-initiated Buprenorphine Treatment

Abstract: Introduction: Medications for opioid use disorder (MOUD), including buprenorphine, represent an evidence-based treatment that supports long-term recovery and reduces risk of overdose death. Patients in crisis from opioid use disorder (OUD) often seek care from emergency departments (ED). The New York Medication for Addiction Treatment and Electronic Referrals (MATTERS) network is designed to support ED-initiated buprenorphine and urgent referrals to long-term care for patients suffering from OUD. Methods: Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Future programmatic implementation should emphasize the education of existing addiction workforce staff on the evidence behind medication-first programs, in which provision of MOUD does not have restrictions or contingencies. 9 , 32 , 33 , 34 When considering research, clinical and policy implications, it is important to know that successful and smooth linkages are possible 6 , 11 , 35 ; however, health systems and programs must be flexible and accommodating, lowering barriers to entry to MOUD and addressing patients’ holistic needs. Linkage to care may be facilitated by recent regulatory changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Future programmatic implementation should emphasize the education of existing addiction workforce staff on the evidence behind medication-first programs, in which provision of MOUD does not have restrictions or contingencies. 9 , 32 , 33 , 34 When considering research, clinical and policy implications, it is important to know that successful and smooth linkages are possible 6 , 11 , 35 ; however, health systems and programs must be flexible and accommodating, lowering barriers to entry to MOUD and addressing patients’ holistic needs. Linkage to care may be facilitated by recent regulatory changes.…”
Section: Discussionmentioning
confidence: 99%
“…Several referral options exist, including linking patients to clinicians in primary care sites, opioid treatment programs (OTPs), substance use disorder treatment centers, or bridge clinics for low-threshold buprenorphine. [9][10][11][12] However, 1 study 13 analyzing pharmacy claims data demonstrated that only 28.5% of patients receiving initial buprenorphine treatment in an ED setting filled a subsequent prescription for buprenorphine from a community-based clinician. Thus, to inform implementation efforts to promote ED-initiated buprenorphine with receipt of ongoing treatment, we explored perspectives of community-based clinicians and staff positioned to potentially receive ED-based referrals for ongoing OUD treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations